Implementation and Sustainability of an Evidence-Based Program: Lessons Learned From the PRISM Applied to First Step to Success. (June 2014) - Woodbridge, Michelle W.; Sumi, W. Carl; Yu, Jennifer; Rouspil, Kristen; Javitz, Harold S.; Seeley, John R.; Walker, Hill M.
Although numerous studies address the efficacy of school-based interventions, fewer focus on how to support sustainability of interventions from the perspective of participants. To address this research gap, we use the Practical, Robust Implementation and Sustainability Model to examine how the characteristics of an evidence-based program interact with those of participants (i.e., students, parents, educators) to influence program implementation and continuation. Specifically, we consider lessons learned in one site of the national effectiveness study of First Step to Success which sustained implementation in a majority of participating schools after the study ceased. First, we analyze implementation fidelity and its effects on students' behavioral and academic outcome data. Then, we analyze focus group and interview data collected from participants 2 years after initial implementation to consider contextual factors associated with continued program success, including (a) the nature of the intervention, (b) the external environment, (c) implementation and sustainability infrastructure, and (d) participant characteristics.